Orientation and optimization: The Dilemma and Practical Path of the Overall Teaching of Chinese Units in Primary Schools. - Wang, Yuanyin (SHS Web of Conferences, 2024)
Under the guidance of core literacy in Chinese, unit based holistic teaching, as a major emerging form of primary school Chinese teaching, has gradually become the focus of current Chinese teaching practice and research. The overall teaching of the unit is based on real task situations, but in the implementation of primary school Chinese teaching, problems such as simplification, formality, and excessive extension have been exposed, which urgently need to be effectively resolved. The overall teaching of units is generated on top of traditional unit teaching, and should be reasonably connected to the foundation of unit teaching, constructing a more coherent learning process, in order to explore the optimization path to achieve the overall teaching goals of units.